Looking for the mechanism of arsenate respiration of Fusibacter sp. strain 3D3, independent of ArrAB - Acosta-Grinok, Mauricio; Vázquez, Susana; Guiliani, Nicolás; Marín, Sabrina; Demergasso, Cecilia (Frontiers in Microbiology, 2022)
The literature has reported the isolation of arsenate-dependent growing microorganisms which lack a canonical homolog for respiratory arsenate reductase, ArrAB. We recently isolated an arsenate-dependent growing bacterium from volcanic arsenic-bearing environments in Northern Chile, Fusibacter sp. strain 3D3 (Fas) and studied the arsenic metabolism in this Gram-positive isolate. Features of Fas deduced from genome analysis and comparative analysis with other arsenate-reducing microorganisms revealed the lack of ArrAB coding genes and the occurrence of two arsC genes encoding for putative cytoplasmic arsenate reductases named ArsC-1 and ArsC-2. Interestingly, ArsC-1 and ArsC-2 belong to the thioredoxin-coupled family (because of the redox-active disulfide protein used as reductant), but they conferred differential arsenate resistance to the E. coli WC3110 DarsC strain. PCR experiments confirmed the absence of arrAB genes and results obtained using uncouplers revealed that Fas growth is linked to the proton gradient. In addition, Fas harbors ferredoxin-NAD+ oxidoreductase (Rnf) and electron transfer flavoprotein coding (etf) coding genes. These are key molecular markers of a recently discovered flavin-based electron bifurcation mechanism involved in energy conservation, mainly in anaerobic metabolisms regulated by the cellular redox state and mostly associated with cytoplasmic enzyme complexes. At least three electron-bifurcating flavoenzyme complexes were evidenced in Fas, some of them shared in conserved genomic regions by other members of the Fusibacter genus. These physiological and genomic findings permit us to hypothesize the existence of an uncharacterized arsenate-dependent growth metabolism regulated by the cellular redox state in the Fusibacter genus.